Structural Planning Assistance for The Rehap of Jabal Nur Mosque, Takimpo Village - Abdu, Muhammad; Asrasal, Aswad; Suherman, La Ode Achmad; Sakinah (Room of Civil Society Development, 2022)
The purpose of community service is to assist the people of Takimpo Village in planning the structure of mosque buildings, so that the village government and mosque committees get an idea of the needs of the main structure in the mosque that is safe both from the condition of plates, beams, or columns. Meanwhile, in determining the structure, it cannot be determined by just any other than a civil engineer who must calculate the needs of both the quality, the dimensions of the repeating roof. To achieve this, the concept of design, structural planning is carried out by a team that carries out service so that the final results obtained are the calculation of the structure and work drawings of the structure of the jabal nur mosque in Takimpo Village, Pasarwajo District, Buton Regency Keywords: civil engineering, structure, work drawings, mosque, takimpo